SOCIAL MEDIA CONSUMPTION AND THE CONSTRUCTION OF IDOL AMONG THE TEENAGERS IN SUBURBAN AREA OF YOGYAKARTA - Rismayanti, Rebekka; Vidiadari, Irene Santika; Ispandriarno, Lukas Suryanto (Interaksi: Jurnal Ilmu Komunikasi, 2022)
The advancement of technology has made many people, including teenagers, use new media to access information and interact with other people. One of the new media platforms widely used by teenagers is social media. Because identity plays a significant role in the life of the youth, besides sexuality, social media is relevant to teenagers. Social media helps teenagers on their quest to define and explore who they are, one of which is by facilitating them to find idols. This research aims at illustrating the construction of idols in teenagers through the consumption of one of the social media platforms, Instagram, by employing a qualitative approach and case-study methods. The research result shows that social media consumption in suburban adolescents is low and makes them still have strong connections with the surrounding social environment. The low consumption and influence of social media also make it easy for teenagers to believe in their idol's appearance and perceive it as a complete image of the idol. Teenagers have many ways to find and 'meet' their idols. Teenagers believe in their idols' social media appearance and perceive that the contents show the natural character and personality of the idols.